A Traffic Management System for Minimization of Intersection Traffic Congestion: Case Bengkong Junction, Batam - Ilham Andika; Andri Irfan Rifai; Muhammad Isradi; Joewono Prasetijo (IJEBD (International Journal of Entrepreneurship and Business Development), 2022)
Purpose: An increase in the number of vehicles that are not matched by the growth of road area is one of the causes of road Traffic congestion in Batam City. Traffic congestion occurs, especially in business and densely populated residential areas. The government has carried out various engineering and traffic management to keep the road service level under control. This study aims to analyze traffic management's efficiency in reducing Traffic congestion on roads in Batam City. Design/methodology/approach: This study uses a case study at the Bengkong red light intersection, Batam City. The analysis was carried out using The Indonesian Highway Capacity Manual-1997. Findings: Traffic management and engineering must be implemented gradually to get a suitable implementation model. Actual conditions in the field become essential in determining the right choice of traffic management and engineering. Research limitations/implications: Traffic management and engineering analyzes were conducted locally at the case study site. Practical implications: The analysis of traffic management reduces traffic congestion's impact. Originality/value: Original paper Paper type: A case study